Mitral valve surgery - Bonser, Robert S.; Pagano, Domenico; Haverich, A. (Axel) 1953-.; SpringerLink (Online service). (London New York Springer, 2011)
Part of the Monographs in "Cardiac Surgery Series"--Introducing 'basic science into the cardiac operating room'. This title includes fast systematic review of small areas of cardiac surgery including up-to-date information. This will allow more rapid publication than the alternative cardiac surgery 'tomes'. This entry into the series will provide readers with a complete review of the current understanding in mitral valve surgery and include extensive details on the diagnosis and surgical management of patients with mitral valve disease.
An appreciation of atrioventricular valve surgical anatomy reveals that they are much more than simple valves, opening and closing in response to pressure changes. The structural interrelationship of the valves of the heart and the dynamic mechanisms involved in their function are fundamental in optimizing valve performance, and are dependent upon an intricate multifaceted central cardiac complex. Mitral Valve Surgery presents a detailed background of the mitral valve, its pathology, evaluation, repair and replacement from a range of experts in the field, providing a detailed reference for clinicians in cardiology, cardiac surgery, interventional cardiology, and related fields. The Editors have designed the book to be a comprehensive and systematic review including current practical information and guidance. As we look to the future, mitral valve surgery will continue to evolve and attempting to maximize patient outcome such injury will become increasingly important. This book provides the fundamental background information to fuel interest, initiate novel prevention, refine surgical and therapeutic strategies, and inform the investigator how to develop and design their research study.
Surgical anatomy of the mitral and tricuspid valve -- Pathology and classification of mitral valve disease -- Chronic mitral regurgitation -- Chronic ischemic mitral regurgitation -- Asymptomatic mitral valve regurgitation: watchful wait or early repair?: review of the current evidence -- Mitral valve prosthesis insertion with preservation of the sub-valvar apparatus -- How I assess and repair the Barlow mitral valve: the respect rather than resect approach -- How I assess and repair the Barlow mitral valve: the edge-to-edge technique -- How I assess and repair the Barlow mitral valve -- Ischemic mitral regurgitation -- Minimally invasive mitral valve surgery -- Mitral stenosis -- Atrial fibrillation: non-surgical management -- Ablation of atrial fibrillation with cardiac surgery -- Tricuspid regurgitation: natural history, assessment, and intervention.
Electronic reproduction.
Keywords: Mitral valve -- Surgery; Mitral valve -- Diseases; Electronic books